Facial blanching after local anesthesia injection: Clinico-anatomical correlation—Review of literature - Amin Rahpeyma (Journal of Cutaneous and Aesthetic Surgery, 2020)
Facial blanching as a complication of local anesthesia is reported in dentistry. Inadvertent arterial penetration and subsequent vasospasm has been accepted as the mechanism of this phenomenon. Most cases occur after inferior alveolar nerve block injection. In this article, five cases are reported after Gow-Gates injection, maxillary nerve block via greater palatine foramen, inferior alveolar nerve block, and maxillary buccal infiltration. It is the largest case series in this topic. Also, clinico-anatomical correlation between facial–mucosal blanching and the site of intra-arterial injection is explained. To the best of our knowledge, partial blanching of the face subsequent to buccal infiltration is reported for the first time in this article. Cutaneous surgeon should be aware of this complication and should not carry out unnecessary treatment.